A Protocol for Evaluating Learning Outcomes Using Reverse Jigsaw and Edpuzzle in Doctoral Business Education: A Q-Methodology Study - Liwen Chen (International Journal of Qualitative Methods)
The aim of this Q-methodology study is to explore the impact of innovative pedagogical interventions, specifically the Reverse Jigsaw and Edpuzzle methods, on the learning outcomes of doctoral business students. The Reverse Jigsaw technique, an innovative collaborative learning strategy, emphasizes information sharing and knowledge integration among students. Edpuzzle, as an interactive video learning platform, engages students by allowing educators to embed questions into videos. These methods are known to significantly enhance learning experiences, particularly in the complex environment of higher education. Conducted over an 18-week Qualitative Research course at a business school, the participant pool will consist of 15 students. Focus group interviews will be conducted to extract insights from the participants, followed by the application of Q-sorting procedures to categorize subjective opinions. The findings from the Q-methodology analysis are expected to reveal a diverse spectrum of perspectives held by the doctoral business students. These insights will provide valuable guidance for educators, curriculum designers, and institutions to refine their teaching strategies in the doctoral business education context. This research contributes to the ongoing discourse in relation to pedagogical innovation, and endeavors to elevate the overall quality of education in this specialized field by shedding light on these nuanced viewpoints.